Mutual termination of contract in construction projects - Jambol, Awang Muhamad (2011)
In the present climate where the construction industry is facing an unprecedented rise in the cost of construction materials, the issue of termination is sometimes foremost on the minds of the contracting parties, especially contractors who have not properly estimated the costs during a project lifecycle. Introduction of the mutual termination clause is intended for use by the parties to an existing contract who may wish to terminate the contract and release each other from the contract. Under this form, the original contract is terminated and the parties enter into a mutual release of the contract as well as of any claims that may be pending by one party against the other. Under the Contract Act 1950, the contract may be discharged by mutual consent of contracting parties according to clause 63 and 64 of the Act. A contract may be discharged by an agreement that it shall no longer bind either party. As it is their agreement which binds the parties, so by their agreement they may be loosed from the contractual tie. Mutual termination agreement unequivocally stated that the parties agreed to a mutual termination subject to the terms and conditions set out therein. The effect of this is that the principle contract is thereby rescinded and the parties thereon are bound by the terms and conditions of the mutual termination agreement. Henceforth, if any claim should arise between the parties it is governed by the mutual termination agreement and not by the principle contract which had expressly been rescinded by mutual consent. A termination by mutual consent is an agreement between employer and the contractor to cease work under the contract. Even though in the mutual termination agreement it is clearly stated that the contractor is not entitled or shall not make any claim or demand for any payment, loss, damages, compensation or whatsoever against the client, however in certain circumstances, the disputes still arise and need to be brought to the court for final judgement.